Embodiment and sense-making in autism - De Jaegher, Hanne (Frontiers in Integrative Neuroscience, 2013)
Traditional functionalist approaches to autism consider cognition, communication, and perception separately, and can only provide piecemeal accounts of autism. Basing an integrative explanation on a single cause or common factor has proven difficult. Traditional theories are also disembodied and methodologically individualistic. In order to overcome these problems, I propose an enactive account of autism. For the enactive approach to cognition embodiment, interaction, and personal experience are central to understanding mind and subjectivity. Enaction defines cognition as sense-making: the way cognitive agents meaningfully connect with their world, based on their needs and goals as self-organizing, self-maintaining, embodied agents. In the social realm, when we interactively coordinate our embodied sense-making, we participate in each other’s sense-making. Thus, social understanding is defined as participatory sense-making. Applying the concepts of enaction to autism, I propose that 1) Sensorimotor particularities in autism translate into a different sense-making and vice versa. Autistic behaviors, e.g. restricted interests, will have sensorimotor correlates, as well as specific significance for autistic people in their context. 2) Socially, a reduced flexibility in interactional coordination can lead to difficulties in participatory sense-making. At the same time, however, seemingly irrelevant autistic behavior can be quite attuned to the interactive context. I illustrate this complexity in the case of echolalia. An enactive account of autism starts from the embodiment, experience, and social interactions of autistic people. Enaction brings together the cognitive, social, experiential, and affective aspects of autism in a coherent framework based on a complex, non-linear multi-causality. On this foundation, bridges can be built between autistic people and their often non-autistic context, and quality of life prospects can be improved.